Quiste Dentígero; Características Radiográficas: Revisión de Literatura - Tinoco Cuenca., María Paula (2024)
Dentigerous cyst is one of the most common types of cyst, often associated with the crown of an unerupted tooth. In this context, this study used a retrospective cohort design and quantitative analysis, analyzing clinical case report literature published between 2019 and 2024. However, it is important to note that the retrospective nature of the study and its reliance on radiographic data present inherent limitations. The results are based on previously collected data and do not involve direct intervention or evaluation of patients. Specifically, the prevalence of odontogenic cysts is identified as 20% in a review of 26 articles, indicating a notable occurrence in the population, with a higher frequency observed in males. Therefore, dentigerous cysts are the most common odontogenic lesions observed in both sexes. As a result, there is considerable evidence to suggest that the maxillary region, particularly the canine region, has a significantly increased likelihood of patients presenting with dentigerous cysts. In addition, these cysts are radiographically diagnosed entities that can be variable in presentation, with a higher frequency observed in males. However, the literature identifies the radicular cyst as the most common cystic entity, a conclusion supported by numerous international studies